Challenges and Opportunities for Dental Education from COVID-19 - Bolei Li; Lei Cheng; Haohao Wang (MDPI AG, 2022)
With the ongoing COVID-19 pandemic, dental education has been profoundly affected by this crisis. First of all, COVID-19 brought physical and psychological health problems to dental students and educators. In addition, both non-clinical teaching and clinical-based training experienced challenges, ranging from fully online educational content to limited dental training, students' research was delayed in achieving project milestones and there was hesitancy in respect of the COVID-19 vaccine. On the other hand, the COVID-19 pandemic has increased the demand for teledentistry and dental emergency treatment, and brought awareness of the advantages and high-speed development of distance education. This review aims to present these challenges and opportunities for dental education, and suggest how dental institutions should prepare for the future demand for dental education.